A deep transfer learning approach for COVID-19 detection and exploring a sense of belonging with Diabetes - Ahmad, Ijaz; Merla, Arcangelo; Ali, Farman; Shah, Babar; AlZubi, Ahmad Ali; AlZubi, Mallak Ahmad (Frontiers in Public Health, 2023)
COVID-19 is an epidemic disease that results in death and significantly affects the elderly and those afflicted with chronic medical conditions. Diabetes medication and high blood glucose levels are significant predictors of COVID-19-related death or disease severity. Diabetic individuals, particularly those with preexisting comorbidities or geriatric patients, are at a higher risk of COVID-19 infection, including hospitalization, ICU admission, and death, than those without Diabetes. Everyone's lives have been significantly changed due to the COVID-19 outbreak. Identifying patients infected with COVID-19 in a timely manner is critical to overcoming this challenge. The Real-Time Polymerase Chain Reaction (RT-PCR) diagnostic assay is currently the gold standard for COVID-19 detection. However, RT-PCR is a time-consuming and costly technique requiring a lab kit that is difficult to get in crises and epidemics. This work suggests the CIDICXR-Net50 model, a ResNet-50-based Transfer Learning (TL) method for COVID-19 detection via Chest X-ray (CXR) image classification. The presented model is developed by substituting the final ResNet-50 classifier layer with a new classification head. The model is trained on 3923 chest X-ray images comprising a substantial dataset of 1360 viral pneumonia, 1363 normal, and 1,200 COVID-19 CXR images. The proposed model's performance is evaluated in contrast to the results of six other innovative pre-trained models. The proposed CIDICXR-Net50 model attained 99.11% accuracy on the provided dataset while maintaining 99.15 % precision and recall. This study also explores potential relationships between Covid-19 and Diabetes.